2017
DOI: 10.1097/aln.0000000000001601
|View full text |Cite
|
Sign up to set email alerts
|

Oral Application of Magnesium-l-Threonate Attenuates Vincristine-induced Allodynia and Hyperalgesia by Normalization of Tumor Necrosis Factor-α/Nuclear Factor-κB Signaling

Abstract: Background Antineoplastic agents, including vincristine, often induce neuropathic pain and magnesium deficiency clinically, but the causal link between them has not been determined. No drug is available for treating this form of neuropathic pain. Methods Injection of vincristine (0.1 mg · kg-1 · day-1, intraperitoneally, for 10 days) was used to induce nociceptive sensitization, which was accessed with von Frey hairs and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 58 publications
6
46
0
Order By: Relevance
“…Previous studies showed that magnesium deficiency in rats, induced by a Mg-depleted diet, showed hyperalgesia, which could be attenuated by supplementation with MgSO 4 [11,12]. Moreover, magnesium deficiency is also associated with the neuropathic pain produced by diabetes [10,45] and chemotherapy agents [24,46]. Although visceral pain differs a lot from neuropathic pain, our present study showed magnesium deficiency in both the serum and CSF of cystitis rats.…”
Section: The Role Of Magnesium Deficiency In Mechanical Allodynia Andsupporting
confidence: 58%
See 3 more Smart Citations
“…Previous studies showed that magnesium deficiency in rats, induced by a Mg-depleted diet, showed hyperalgesia, which could be attenuated by supplementation with MgSO 4 [11,12]. Moreover, magnesium deficiency is also associated with the neuropathic pain produced by diabetes [10,45] and chemotherapy agents [24,46]. Although visceral pain differs a lot from neuropathic pain, our present study showed magnesium deficiency in both the serum and CSF of cystitis rats.…”
Section: The Role Of Magnesium Deficiency In Mechanical Allodynia Andsupporting
confidence: 58%
“…A previous study indicated that L-TAMS attenuated vincristine-induced allodynia via inhibition of TNF-α/ NF-κB signaling [38] in the SDH, and could restore memory deficits in spare nerve injury (SNI) rats through inhibition of TNF-α at a hippocampal level [14]. Combined with the upregulation of TNF-α/NF-κB signaling and IL-1β found in both the SDH and hippocampus of cystitis model rats, we hypothesized that oral application of L-TAMS could attenuate mechanical allodynia, memory deficits, and depressive-like behaviors through inhibition of TNF-α/NF-κB signaling and IL-1β in the SDH and hippocampus of cystitis rats.…”
Section: Oral Application Of L-tams Inhibits the Upregulation Of Tnf-mentioning
confidence: 99%
See 2 more Smart Citations
“…The present work provides evidence supporting the hypothesis that induction of LTP at synapses between afferent C-fibers and dorsal horn neurons by 10 V HFS is associated with mechanical allodynia lasting for 50 days in rats (Figure S2B) and more than 35 days in mice ( Figure 4E) as well as thermal hyperalgesia for around 14 days ( Figure 1H). A microglial BDNF-dependent increase in (or sprouting of) CGRP terminals, which is found in a variety of chronic pain conditions (Christensen and Hulsebosch, 1997;Xu et al, 2017;Zheng et al, 2008), serves as a structural basis of the chronic pain. Our finding is also clinically important because chronic pain, unlike acute pain, rarely has an identifiable temporal and causal relationship with injury or disease in the body.…”
Section: Discussionmentioning
confidence: 99%